Effects of fertilizer application on the bacterial community and weathering characteristics of typical purple parent rocks - Wang, Xuan; Zhao, Jixia; Li, Chunpei; Deng, Limei; Cui, Rongyang; Zhou, Tao; Hussain, Zakir; Liu, Gangcai (Frontiers in Microbiology, 2025)
IntroductionRock weathering is a fundamental process that shapes Earth’s topography, soil formation, and other surface processes. However, the mechanisms underlying the influence of fertilizer application on weathering remain poorly understood, especially with respect to bacterial intervention.MethodsIn this study, purple parent rocks from Shaximiao Group (J2s) and Penglaizhen Group (J3p) were selected to investigate the effects of fertilizer application on the bacterial community and weathering characteristics of these rock by leaching experiment.ResultsThe results revealed that: fertilizer application, especially when at high levels, greatly altered the abundance, diversity and composition of the bacterial community in weathered products. Through redundancy analysis, a decrease in pH and increases in available nutrients (AN and AP) resulting from fertilizer application were identified as the key factors driving changes of bacterial community composition in weathered products. Moreover, fertilizer application promotes the physical and chemical weathering of the parent rocks to some extent. This is especially true for the chemical weathering of J2s. Structural equation model indicated that fertilizer application affects weathering through multiple pathways by affecting the chemical properties (pH, C:N and AP), specific bacterial genera (IMCC26256, Ramlibacter, and Nitrosospira), and bacterial community composition of weathered products.DiscussionOur study links weathering characteristics with chemical properties and bacterial community changes of weathered products after fertilizer application, which plays a key role in controlling and predicting dynamic changes of rock weathering in space and time. It is helpful to further understand the law of human activities affecting the surface processes.